The Effect of Implementing Accounting Information Systems on the Internal Control Efficiency in the commercial banking sector in the Kingdom of Saudi Arabia - Qutb, Reem Bakr; Obaid, Rawia Reza (Journal of Economic, Administrative and Legal Sciences, 2019)
This study aimed to examine the impact of accounting information systems on the efficiency of internal control in the commercial banking sector in Saudi Arabia. The accounting information systems are the main engine and infrastructure of contemporary management and the main source of information. This topic was chosen for its importance, which stems from the importance of the efficiency of internal control, whether for researchers, workers or stock holders in a key sector (banks). In terms of the methodology of the study; the study relied on the inductive method in the theoretical review. In the application framework, the analytical descriptive method was adopted. The study data were collected by means of the research tool represented in the questionnaire. A sample of the study was presented by the staff of the commercial banks in Saudi Arabia. The SPSS program was used to analyze the study data. The most important results of the study, the existence of a clear objective of accounting information systems according to the views of the sample study. Internal control is one of its first goals and concerns that it is based on protecting the bank’s assets. One of the main implications of the use of accounting information systems in the effectiveness of internal control is to contribute to the provision of indicators and standards that assist management in detecting financial deviations to assist the internal control department of banks.